Contamination of digital evidence: Understanding an underexposed risk. (March 2023) - Gruber, Jan; Hargreaves, Christopher J.; Freiling, Felix C.
Abstract: The dangers of contamination have received considerable attention in the literature regarding the investigation of physical crime scenes and physical evidence. The understanding of contamination in the context of digital evidence appears to be much less understood. Based on experiences from the field of physical evidence, we develop a generalized definition of contamination that also covers digital evidence, namely the "inadvertent transfer of traits to an object of relevance at any point in the forensic process". We illustrate the definition by presenting several examples and counterexamples for contamination of digital evidence. By addressing the specifics of digital evidence in this context, we argue that our definition can be useful to understand the risks arising through contamination in this domain.